The Path to the Rule of Law—An Overall Review of Legal Reform, Crime and the Judicial System During the Transition Era in China. (January 2020) - Qi, Ziwei
In order to understand crime and the legal system in the People's Republic of China (P.R.C.), it is necessary to understand the components of a crime and the structure of the judicial system in the P.R.C. By examining the elements of crime from the written criminal code and by analysing the structure of the judicial system, we will find some procedural and substantive challenges to appeal, which might contradict the philosophy of unbiased judicial principles. The article also explores possible social and political forces that might affect the direction of legal reform in China. The author aims to provide the readers with a basic overview of the judicial system in China and the social forces behind the current legal reform towards the rule of law.